Numerical Solution of the Heat Accumulator Layer by Means of FEM - Pavel Fiala; Ivo Behunek; Eva Kadlecova (Advances in Electrical and Electronic Engineering, 2006)
The article deals with one layer of a heat accumulator which is suitable for solar systems. There is a description of the air turbulence, heat transfer, conduction and also phase change of CaCl2.6H2O which is used to increase the density of stored energy. The numerical solution was done with the help of finite element method (FEM) in ANSYS software.